COVID-19 Antibody Surveillance Among Healthcare Workers in A Non-COVID designated Cardiology Centre - Ling, Hwei Sung; Pang, Ing Xiang; Fong, Alan Yean Yip; Ong, Tiong Kiam; Khiew, Ning Zhang; Cham, Yee Ling; Asri, Said; Oon, Yen Yee; Koh, Keng Tat; Tan, Chen Ting; Ho, Kian Hui; Shu, Francis Eng Pbeng; et al. (2020)
BACKGROUND: Reports on healthcare worker antibody response to COVID-19 infection are scarce. We aim to determine theCOVID-19 antibody prevalence among healthcare workers in a cardiology centre and the relationship between case definitioncriteria with the COVID-19 antibody result. METHODS: Convenience sampling was applied. Healthcare workers in SarawakHeart Centre (SHC) cardiology, radiology, and emergency unit were recruited. A survey form on clinical symptoms and closecontact history was distributed. HEALGEN COVID-19 IgG/IgM rapid test was performed using serum/ whole blood specimen.Staff with positive COVID-19 antibody results were referred to the infectious disease specialist for assessment. RESULTS: Atotal of 310 staff were screened. 220(71%) were female, and the mean age was 36±7.7 years old. 46(14.8%) staff reported havingclinical symptoms at some stage from the end of January 2020 to the time of this surveillance. Number of staff who had a historyof overseas travel, close contact with confirmed COVID-19 patients, or had visited places with identified COVID-19 clusterswere 4(1.3%), 24(7.7%) and 24(7.7%) respectively. There were 14 staff (4.5%) with positive tests positive, 2 for IgM, and 12for IgG. All those with positive antibody were subsequently tested negative with RT-PCR test. The history of having clinicalsymptoms and exposure to COVID-19 cluster area were independently associated with a positive IgG result. CONCLUSION:The application of COVID-19 antibody serology rapid tests could determine true exposure of staff to the infection and allowus to reassess existing measures of infection control within the hospital.